Variational and reciprocal principles in two-temperature generalized thermoelasticity - Kumar R.; Prasad R.; Mukhopadhyay S. (My University, 2025)
The aim of the present work is to establish a variational principle of convolutional type and a reciprocal principle in the context of linear theory of two-temperature generalized thermoelasticity, for a homogeneous and isotropic body.